2017
DOI: 10.1103/physreva.96.033827
|View full text |Cite
|
Sign up to set email alerts
|

Bloch oscillations and resonant radiation of light propagating in arrays of nonlinear fibers with high-order dispersion

Abstract: Bloch oscillations of spatio-temporal light wave packets in arrays of nonlinear fibers with highorder dispersion are studied. The light wave experiences discrete spatial diffraction along the waveguide array coordinate together with continuous temporal dispersion including higher order terms. When a gradient in the waveguide light confinement strength is considered, the wave packet features robust long-lived Bloch oscillations with temporal and spatial spreading in the presence of a Kerr nonlinearity. The effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Propagation of oscillating solitons in the presence of high order dispersion was studied experimentally and numerically and very rich dynamics of the solitons was reported [35][36][37][38] . Cherenkov radiation of oscillating cavity solitons was recently considered 39 but the effect of the synchrotron radiation was out of the scope of that paper.…”
mentioning
confidence: 99%
“…Propagation of oscillating solitons in the presence of high order dispersion was studied experimentally and numerically and very rich dynamics of the solitons was reported [35][36][37][38] . Cherenkov radiation of oscillating cavity solitons was recently considered 39 but the effect of the synchrotron radiation was out of the scope of that paper.…”
mentioning
confidence: 99%
“…This understanding allowed to suggest different, sometimes quite complicated methods of nonlinearity management stabilizing Bloch oscillations in the nonlinear regime [50][51][52][53]. It was also found that, quite surprisingly, the increase of the dimensionality of the system can also stabilize Bloch oscillations [54] making possible, for instance, their use for resonant new frequency generation [55].…”
Section: Introductionmentioning
confidence: 91%
“…Thus, one may expect the existence of a new species of robust nonlinear hybrid wave packets, combining features of solitons and Blochoscillating waves. In photonic systems, the robustness of the hybrid wave packets in the presence of the anomalous group-velocity dispersion may lead to prediction of resonant radiation with nontrivial properties, similar to how it was predicted in the spatial domain under the action of diffraction [8]. This methodology is conceptually different from several proposed ways to guide nonlinear waves experiencing BOs in nonlinear regime that include variation of nonlinear interactions strength along the evolution [9,10].…”
Section: Introductionmentioning
confidence: 99%